2022
DOI: 10.3390/ijms23169071
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stem Cells-Induced Trophoblast Invasion Is Reduced in Patients with a Previous History of Preeclampsia

Abstract: Endometrial stromal cells play an important role in reproductive success, especially in implantation and placentation. Although Mesenchymal stem cells (MSCs) have been studied to assess decidualization disorders in preeclampsia (PE), their role during trophoblast invasion remains unclear. This study aims to determine: (i) whether MSCs isolated from menstrual fluid (MenSCs) from nulliparous, multiparous, and women with a previous history of preeclampsia exhibited different patterns of proliferation and migratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 37 publications
1
9
0
Order By: Relevance
“…Successful implantation requires effective maternal-embryonic communication [2][3][4]27]. Using an in vitro 3D trophoblast invasion model, we have confirmed that trophoblast cells were only able to migrate from the trophosphere and invade through the MATRIGEL in the presence of MenSCs of endometrial origin, which was pre-treated with the endometrial mimic, suggesting that MenSCs secrete important factors that trigger the motility and invasion of the trophoblast cells, as described previously [10,23,24]. More importantly, FOXM1 mRNA expression was significantly higher in those trophoblast cells that invaded greater into the MATRIGEL, i.e., the trophospheres that were co-cultured with MATRIGEL and MenSCs compared to pre-invasion trophospheres.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Successful implantation requires effective maternal-embryonic communication [2][3][4]27]. Using an in vitro 3D trophoblast invasion model, we have confirmed that trophoblast cells were only able to migrate from the trophosphere and invade through the MATRIGEL in the presence of MenSCs of endometrial origin, which was pre-treated with the endometrial mimic, suggesting that MenSCs secrete important factors that trigger the motility and invasion of the trophoblast cells, as described previously [10,23,24]. More importantly, FOXM1 mRNA expression was significantly higher in those trophoblast cells that invaded greater into the MATRIGEL, i.e., the trophospheres that were co-cultured with MATRIGEL and MenSCs compared to pre-invasion trophospheres.…”
Section: Discussionsupporting
confidence: 80%
“…During implantation, trophoblast invasion of the uterine lining depends on the communication between the trophectoderm and the maternal decidua and involves the migration and invasion of the trophoblast cells from out of the blastocyst and through various layers of the endometrium, accompanied by the degradation of the extracellular matrix and stroma [5,10]. In order to understand whether FOXM1 is involved in trophoblast invasion during implantation, we used an in vitro 3D trophoblast invasion model [23,24] that mimics the processes of migration and early invasion of the trophoblast and assessed the expression of FOXM1 in trophoblast cells. This assay consists of generating, in vitro, blastocyst like-structures (trophospheres) and co-culturing them onto a layer of MATRIGEL and mesenchymal stem cells isolated from menstrual fluid (MenSCs), mimicking the extracellular matrix and the endometrial stromal cells, respectively (Figure 4A).…”
Section: Foxm1 Is Involved In Early Invasion Of the Trophoblastmentioning
confidence: 99%
“…37 Current opinions support the view that trophoblast cell invasion is crucial for the development of PE. 3840 The current experimental results demonstrated that PPP1R3G knockdown suppressed the proliferation, invasion, and migration abilities, but had no discernible effect on apoptosis in HTR-8/SVneo trophoblast cells. Thus, it can be speculated that PPP1R3G might be involved in the pathogenesis of PE through modulating trophoblast cell behavior.…”
Section: Discussionmentioning
confidence: 66%
“…Salomon et al [21] found 12 differentially expressed exosome miRNAs between normal pregnancy and preeclampsia pregnancy, among which the increased expression levels of miR-486-1-5p and miR-486-2-5p were most significant in the preeclampsia group. To sum up, changes in miRNA content in exosomes lead to abnormal cell growth, adhesion, migration and invasion, and ultimately affect endothelial cells, resulting in systemic endothelial dysfunction and impaired angiogenesis [22] . The current study is still limited, and more studies are needed to further clarify the differences in expression and mechanism of action of these miRNAs in preeclampsia.…”
Section: Exosomes Derived From Placental Mesenchymal Stem Cells and P...mentioning
confidence: 99%